2008
DOI: 10.1152/ajprenal.90441.2008
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide: vasoconstrictor or vasodilator? That's the question

Abstract: A STUDY BY BOTROS ET AL. (3) provides evidence that induction of renal heme oxygenase-1 (HO-1) attenuates afferent arterioles (Aff-Art) constrictor responses to increased renal perfusion pressure (RPP), thus suggesting that increased HO-1 modulates renal autoregulation in pathophysiological conditions. The authors elegantly made their conclusions by first showing the HO-1 pattern distribution following heme or SnCl 2 treatment. In particular, the authors demonstrated that in hemin-treated rats HO-1 was express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Some investigators suggested that CO promotes endothelium-dependent vasoconstriction by inhibiting NO production [28] at vascular level. This is especially true for exogenous CO, as in cases of intoxication [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggested that CO promotes endothelium-dependent vasoconstriction by inhibiting NO production [28] at vascular level. This is especially true for exogenous CO, as in cases of intoxication [29].…”
Section: Discussionmentioning
confidence: 99%